Impact of a Cooperative Society on the Arecanut Marketing in Kerala — A Case Study of Central Arecanut Marketing and Processing Cooperative Ltd - N. Karunakaran (Agricultural Economics Research Review, 2014)
The marketing system of arecanut in Kerala includes primary, secondary and terminal markets. The trade in arecanut was monopolistic in nature. But this has changed since mid-1970s as a result of formation of a co-operative society called Central Arecanut Marketing and Processing Co-operative Ltd (CAMPCO). The establishment of CAMPCO has raised the farm price and wholesale price of arecanut in Kerala, of course with minor fluctuations. Arecanut marketing channel involves a number of market intermediaries. Most of the produce passes through village traders, itinerant merchants, private wholesalers, the CAMPCO and the retailers. A lower price spread and a better price through CAMPCO to arecanut growers among different marketing channels in Kerala is the most important impact of this co-operative venture. The CAMPCO has also educated the growers on the grading of arecanut in a scientific manner according to its size and quality. All these effects of CAMPCO have made arecanut cultivation more remunerative and has improved the economic status of arecanut farmers.